Research Trends in the Analysis of Elementary Level Arabic Textbooks: Systematic Literature Review - Sodik, Achmad Ja'far; Sutaman, Sutaman; Arifa, Zakiyah; Nurmala, Mia (Borneo Journal of Language and Education, 2024)
Research study about the research trends in the analysis of elementary level arabic textbooks is very important. This is based on the large number of studies in arabic language journals that examine analytical research on arabic textbooks. The purpose of this study is first to map research studies on the analysis of Arabic language textbooks at the elementary level in Arabic language journals in Indonesia in the period 2018 to 2022 in terms of year of publication, journal category, and first author's institution on articles. The second is to analyze research studies on the analysis of Arabic textbooks at the basic level from the point of view of problem formulation. The type of research in this research is a systematic literature review using the PRISMA type method (preferred reporting items for systematic reviews and meta-analyses). The procedure in this study includes 4 stages, namely identification, screening, eligibility, and include. The results of this study indicate that a research study on the trend of research on elementary level Arabic textbook analysis in the 2018-2022 period can be classified into 2 findings. The first is in terms of the identity of the article which includes three things, namely the year the article was published, the journal category in the article, and the institution/organization of the first author of the article. Second, in terms of the formulation of the problem, which resulted in the scope of research on the tendency of the analysis of Arabic textbooks to focus only on the suitability analysis of Arabic textbook materials, namely conformity with the curriculum, approach, BSNP, and 5C ACTFL.